Political Social Work - Lane, Shannon R.; Pritzker, Suzanne (Springer, 2018)
Both authors come to this book after many years both of professional practice in the political arena and of teaching and researching about political engagement. Shannon pursued a political social work career for over a decade at the federal level in the U.S. Senate. Suzanne began her career in policy at the state level in Virginia before entering the field of social work, in order to be a part of a profession that is committed to creating a more accessible and inclusive policy environment where more diverse voices are represented. We have both continued to advocate for social change at the state and federal level throughout our academic careers. While our backgrounds and professional experiences in policy and politics are different, we share a strong commitment to the power of political engagement to bring about more responsive and more just policies. We are both firmly convinced that social workers can and should be at the forefront of efforts to expand political engagement and to bring about political change. Building on that commitment, this book discusses the many opportunities for social workers to participate and lead in the political arena. This book marries the social work profession’s ethical imperative to pursue political action, individual social workers’ passion for the populations and communities with whom we work, and effective strategies and tools to move both our ethical imperative and our passions into action. Combining the generalist skills and knowledge that social workers develop through their education and practice with political knowledge and skills lays the groundwork for strong and effective efforts to influence and shape policy. We have written this book to support both social work students and professional social workers in expanding their own political participation. We identify and explore five domains of political social work practice—each of which social workers may engage in either as full-time political social work practitioners or as complementary to their social work practice in clinical, community, or administrative settings. In our classrooms and in the field, we have frequently heard students and practitioners ask for examples and models of what political social work practice might look like. We incorporate profiles of real-life social workers whose work has inspired us, and who offer models of political social work practice in each domain.
Using Power to Create Social Change